Correlation between rumination and postpartum depression of puerperal women (产妇产后抑郁与其反刍思维的相关性分析) - GAO Siyu (高丝雨); LIU Fang (刘芳); LI Xiaowei (李晓伟); ZHANG Qiaoling (张巧玲); YANG Lei (杨磊) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the correlation between postpartum depression and rumination among puerperal women. Methods From October 2021 to February 2022, 260 puerperal women in three grade 3 hospitals of Xi 'an were selected by convenience sampling method for postpartum review. The Edinburgh Postnatal Depression Scale (EPDS) was used to investigate postpartum depression. Puerperal women were divided into two groups according to their EPDS score (EPDS≥10 in depressed group, EPDS＜10 in non-depressed group). The Ruminative Responses Scale (RRS) scores were compared between the depressed group and the non-depressed group, and the correlation analysis were conducted between postpartum depression and rumination. Results The average score of EPDS in 260 puerperal women was (6. 83±2. 75), and the incidence of postpartum depression was 21. 15%(55/260). The total score of RRS and the score of every dimension in the depressed group were higher than those in the non-depressed group (P<0. 01). Postpartum depression was positively correlated with rumination (r=0. 843, P<0. 01). Conclusion The higher the rumination, the higher the depression tendency. Rumination can prevent and reduce the occurrence of postpartum depression by reducing rumination level. (目的 探讨产妇产后抑郁与其反刍思维间的相关性。方法 2021年10月-2022年2月, 采用便利抽样法选取西安市3所三级甲等医院产后复查的260名产妇为研究对象, 采用爱丁堡产后抑郁量表(EPDS)调查产妇产后抑郁情况, 以EPDS≥10为界划分为两组, 比较抑郁组产妇与无抑郁组反刍思维反应量表(RRS)评分, 并进行产后抑郁与反刍思维的相关性分析。结果 260名产妇产后EPDS量表平均得分为(6. 83±2. 75)分, 产后抑郁发生率为21. 15%(55/260); 抑郁组产妇RRS量表总得分及各维度评分均高于无抑郁组产妇(P＜0. 01); 产后抑郁与反刍思维呈正相关(r=0. 843, P＜0. 01)。结论 产妇反刍思维越高产后抑郁发生越高, 医护人员可通过降低反刍思维来预防和减少产后抑郁的发生。)